Norway-Russia disaster diplomacy for Svalbard - Kelman, Ilan; Sydnes, Are K.; Duda, Patrizia Isabelle; Nikitina, Elena; Webersik, Christian (Safety Science, 2020)
The Arctic is frequently framed as a region of disaster and conflict, as well as of opportunity and cooperation. Disaster diplomacy is one approach for examining how dealing with disasters might or might not affect conflict and cooperation, yet little work on Arctic disaster diplomacy has been completed, especially regarding specific bilateral relations. This paper contributes to filling in this gap by focusing on the post-USSR era to provide the first examination of the prospects and relevance of Norway-Russia disaster-related interaction for the Svalbard archipelago. As a discussion paper focusing on one case study, Norway-Russia disaster diplomacy is analysed in the context of Svalbard followed by potential prospects for Norway-Russia relations to be influenced by Svalbard’s disaster-related activities. Possible meanings for Norway-Russia relations are then discussed. No indication is found that disaster-related activities for or around Svalbard are influencing or could influence Norway-Russia relations or that disaster-related activities are nudging or could push the diplomacy in new and lasting directions. As such, this Arctic case study supports the current disaster diplomacy conclusions that disaster-related activities are sometimes used to spur on existing processes, but have not yet shown to produce any different directions in conflict or cooperation.